Distributed network booting using a BitTorrent-like protocol - Oliveros, Wigi Vei A.
Network booting is widely used today, mostly for thin-client computing, cluster computing, and operating system installation. Popular protocols like trivial file transfer protocol (TFTP) and hypertext transfer protocol (HTTP) are used to download operating system images. Network booting clients simultaneously downloading from a single server create a bottleneck at the servers link once the link capacity has been maximized. The result is a slowdown in the download time and the overall boot process. Several P2P network booting solutions exist, but they only run on top of an already running operating system. In this research, we propose a distributed downloading scheme at the network bootloader level using a BitTorrent-like protocol for networking booting clients. We discuss the implementation of a new download protocol for iPXE, an open-source network bootloader, and evaluate the performances of TFTP, HTTP, and the proposed BitTorrent-like protocol by measuring their download times over varying file sizes and number of nodes. We also measured the amount of server traffic and the protocol overhead generated by the protocols. On 20 clients, simultaneously downloading a 500MiB file using the proposed protocol resulted to a decrease in average download time of 51.6% compared to TFTP and 46.6% compared to HTTP.